Pemenuhan Kewajiban Suami Penyandang Disabilitas Intelektual (Tunagrahita) dalam Membentuk Keluarga Sakinah - Picy Lestari; Rif'ah Roihanah (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2021)
In this world not all humans have normal conditions in terms of quality and quantity of their limbs. Such is the case with families with intellectual disabilities (tunagrahita) in Jambon, Ponorogo. In such conditions, people with disabilities need improvisation and variety in managing and managing their household because if seen from their intellectual abilities they are not able to become leaders in the family. The purpose of this study was to determine the role and review of Islamic law in fulfilling the obligations of husbands with intellectual disabilities (tunagrahita) to form a Sakinah family. The type of research carried out is field research using qualitative methods, while data collection techniques used are interviews and observations. The conclusion of this study is that the husband's role in earning the main living is included in the mu'sir group, the parties who are obliged to help are relatives, the state or wealthy Muslims. And for his role as a leader in the family, this husband with intellectual disability (tunagrahita) cannot be burdened with taklif law, especially Ahliyyah Al'ada'. So external factors (family, relatives, and others) are more dominant in them in forming a sakinah family.